2015
DOI: 10.3233/bme-151274
|View full text |Cite
|
Sign up to set email alerts
|

Luting of CAD/CAM ceramic inlays: Direct composite versus dual-cure luting cement

Abstract: Running short head: Luting of CAD/CAM ceramic inlays 2Corresponding author: Atsushi Kameyama, Division of General Dentistry, Department of Clinical Oral Health Science, Tokyo Dental College, Abstract. The aim of this study was to investigate bonding effectiveness in direct restorations. A two-step self-etch adhesive and a light-cure resin composite was compared with luting with a conventional dual-cure resin cement and a two-step etch and rinse adhesive. Class-I box-type cavities were prepared. Identical cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…Fractures of ceramic (5.6-11%) and marginal defects (12-20%) were the typical reasons for failure [3,4,[6][7][8][9][10][11][12]. In addition to surface conditioning, resin cement can play an important role as seen in previous studies where there was a significantly positive effect of a direct composite as a cement in comparison to different dual-polymerized cements [28,29]. For this reason, this study was undertaken in order to compare photo-polymerizing resin composite to a direct composite as a luting material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractures of ceramic (5.6-11%) and marginal defects (12-20%) were the typical reasons for failure [3,4,[6][7][8][9][10][11][12]. In addition to surface conditioning, resin cement can play an important role as seen in previous studies where there was a significantly positive effect of a direct composite as a cement in comparison to different dual-polymerized cements [28,29]. For this reason, this study was undertaken in order to compare photo-polymerizing resin composite to a direct composite as a luting material.…”
Section: Discussionmentioning
confidence: 99%
“…Using micro-tensile adhesion tests, comparison was made between dual-polymerized resin cements and a direct resin composite but their adhesion was not compared for the application of LVs [24,28]. In a study by Sarr et al, direct resin composite using a regular bonding system resulted in higher microtensile bond strength to dentin when compared to the frequently used, etch and rinse, self-etch or self adhesive resin cements [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the bonding performances of these materials to enamel and dentin [15,16]. However, no studies have evaluated the repair of CAD/CAM ceramic blocks or the related bonding efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The width and thickness of each specimen was measured to the nearest 0.01 mm using a digital caliper (CD-15 CPX, Mitutoyo, Tokyo, Japan), which was used to determine the microtensile bond strength (µTBS, MPa) by dividing the recorded force (N) at the time of fracture by the bond area (mm 2 ). If a specimen failed before proper testing, a bond strength of 0 MPa was used for statistical analyses [14,15]. The actual number of pre-testing failures was explicitly noted, as well.…”
Section: Microtensile Bond Strength (µTbs) Testingmentioning
confidence: 99%